Real-world effectiveness and safety of fingolimod in patients with multiple sclerosis in the Czech Republic: results from core and extension parts of the GOLEMS study up to 48 months - Tichá, Veronika; Počíková, Zuzana; Vytlačil, Josef; Štěpánová, Radka (BMC neurology, 2022)
BACKGROUND: Fingolimod, an oral sphingosine 1-phosphate receptor immunomodulator, is approved in Europe for people with multiple sclerosis (pwMS) with highly active disease despite a full and adequate course of treatment with ≥ 1 disease-modifying therapy or patients with rapidly evolving severe relapsing-remitting MS. GOLEMS, a national, multicenter, non-interventional, single-arm, real-world study showed a favorable benefit-risk profile of 12-month treatment with fingolimod in pwMS in the Czech Republic. Here, we evaluated the long-term effectiveness and safety of fingolimod and its impact on disability progression and work capability for up to 48 months in pwMS. METHODS: The endpoints assessed were the incidence and severity of MS relapses in fingolimod-treated patients and the proportion of relapse-free patients up to 48 months of fingolimod treatment, change from baseline in the Expanded Disability Status Scale (EDSS) score, and change from baseline in work capability assessment. Efficacy outcomes were analyzed in the completed and efficacy sets, and safety was evaluated in all the enrolled patients. RESULTS: Of 240 enrolled patients, 237 were included into efficacy set. Patients with a minimum of a 12-month observation period in the core study who continued fingolimod treatment, were eligible to participate in the extension phase. Of 211 patients enrolled in extension study, 155 were evaluated in the completed set. Based on analysis of 48-month period of fingolimod treatment, 95/237 patients (40.1%) in the efficacy set, 54/155 (34.8%) in the completed set were free of relapses. The majority of relapses reported were moderate in intensity. Mean EDSS score remained stable throughout 48-month study period (Baseline, 3.4; Month 48, 3.6). No trend was observed in changes in work capability assessment or number of missed days of work. Of 240 enrolled patients, 147 (61.3%) had ≥ 1 treatment-emergent adverse event (AE) and 20 (8.3%) reported serious AEs. In total, 45 patients (18.8%) permanently discontinued treatment because of AEs related to study drug; two patients reported pregnancy after treatment initiation and subsequently discontinued the treatment; no deaths were reported. CONCLUSION: GOLEMS study demonstrated the sustained effectiveness and manageable safety profile of fingolimod under real-world conditions over 48 months in patients with MS. TRIAL REGISTRATION: Not applicable.
Keywords: recidiva; Humans; Multiple Sclerosis; Relapse; GOLEMS extension study; výsledek terapie; Fingolimod; lidé; EDSS score; imunosupresiva; fingolimod hydrochlorid; Immunosuppressive Agents; Multiple sclerosis; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; roztroušená skleróza; Treatment Outcome; Czech Republic; Fingolimod Hydrochloride; Recurrence; Česká republika